STRATEGI PROMOSI KERAJINAN BATIK KAYU DESA WISATA KREBET - , RICKY JULIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Krebet tourism village located in Sendangsari,pajangan, Bantul, Yogyakarta . The village has a population of Â± 800 Â± Soul with an area of 104 hectares , in the form of ground limestoneand consists of moor and yard that stretches from RT 01 to RT 05 . Tourist attractions in the Krebet village is nature tourism for example : Grujugan pulosari,Krebet tree , outbound , how to grow crops and landscapes viewed from a hill Displays, while cultural tourism like a : batik wood , Jathilan, musical traditional and Merti dusun. Facilities available in there is home stay , Musholah , public toilets , where parki . The majority of citizen in Krebet Village working acting a craftmen Batik wood. Batik Wood Art Krebet Tourism Village given fositif contribute greatly to the local people, especially in economicterms. Data collection techniques used in this research that the interview technique, Literature Study and Field Observations and descriptive and qualitative research method in which researchers can describe the phenomenon exists and presents facts systematically to easy understanding and conclusion. From the results it can be concluded thatthe field of 54 to the studio craft of Batik Wood Krebet tourist village just a few studios are already doing promotion strategy with online media and print media studio craft even a fraction does not promote the craft so that the sales are just waiting for tourists who come to the village is to simply buy souvenirs of Batik Wood or enjoy the tourist attractions located in the tourism Krebet village.